Análise da segurança hídrica no Estado do Ceará: subsídios para o planejamento e gestão dos Recursos Hídricos - Rabelo, Nosliana Nobre (2022)
The term Water Security has emerged as a way to support the planning of water resources to more effective results in order to guarantee the availability of water for various uses, meeting the needs of society, as well as protecting it against the impacts caused by climate change. Since the Hague Conference in 2000, local governments have taken on greater responsibilities in debates and practices related to promoting water security (SH). This context became more evident due to the concern of the international community with the scarcity of water resources in the face of the negative effects of extreme hydrological events, as these threaten water supply systems; economic development; and the loss of biodiversity. In Brazil, it can be said that Federal Law No. 9,433/1997, which instituted the National Water Resources Policy (PNRH), and similar state laws bring together the concept of SH. However, from 2014 onwards, this definition gained notoriety due to the water crisis experienced in several regions of the country, mainly in the Southeast, which ended up placing the issue on the national agenda. Therefore, the general objective of the thesis was to analyze the water security of Ceará's municipalities from a multidimensional perspective, generating subsidies for the planning and management of water resources. To achieve this objective, the following methods were adopted: i) creation of the aggregate index: the Water Security Index (ISHCE), through Factor Analysis (FA) by the Principal Components Method (PCA); ii) cluster analysis, using the K-means method, to segment the classes of municipalities according to SH levels; and iii) quantile regression, which sought to capture how water security can influence development on a municipal scale. Thus, the study started from the hypothesis that the municipalities of Ceará have low levels of water security, in almost all dimensions, since they have few structures to manage this issue. In this sense and from the results, it was possible to point to the fact that the state of Ceará is heterogeneous in terms of water security, since it was possible to classify the municipalities into three different levels of water security. This reality is mainly perceived when viewing that of the 176 municipalities analyzed, 33.52% of them had an above-average water security index, and another 13.63% had a below-average index.